Pengenalan Keselamatan, Kesehatan Kerja dan Lingkungan (K3L) serta Perilaku Hidup Sehat dengan penerapan Zero Waste - Agus Susanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
AKS Ibu Kartini is a Vocational College where 80% of student activities are in work laboratories which are at risk of work accidents, so it is necessary to conduct outreach on the introduction of Occupational Safety, Health and the Environment (K3L). The aim of the outreach is for participants to know and apply K3L at work to improve health, minimize work risks, create a healthy work environment, and increase work productivity and healthy living behavior with Zero Waste. The methods used for socialization are interactive lectures, Javanese questions and discussions.Training on introducing Safety, Occupational Health and the Environment (K3L) and Healthy Living Behavior with Zero Waste was given to semester 1 students during the Introduction to New Student Campus Life (PKKMB) activity. This training begins with filling in the participant attendance list, then officially opening the activity, providing materials, followed by questions and answers and discussion, then ends with a group photo. The level of success of this training can be concluded through 2 (two) indicators, namely participant enthusiasm and student enthusiasm in the smooth running of this socialization activity, starting from the preparation process to implementation and participants having knowledge in answering quizzes